World Economic Outlook, October 1991. (World Economic Outlook; World Economic Outlook ;, 1991)
This paper highlights that the growth of world economic activity in 1991 is expected to fall to a scant 1 percent, the lowest in any year since 1982, when the industrial economies were in recession. The slowdown in the expansion of world trade would be considerably more pronounced. Output growth in the industrial countries as a group is expected to average 1u percent in 1991, reflecting a fall in economic activity in a number of countries. Cyclical divergences among the major countries persisted in the first half of 1991.